Students' and patients' perceptions of clinical learning in primary health care - Eva Öhman (2024)
BackgroundClinical practice is an important part of medical education, providing students with an opportunity to put theory into practice and develop clinical skills. Primary health care (PHC) has gained increasing importance for students' development of clinical skills and provides a place where students can prepare for their future profession under supervision. The clinical learning environment in PHC is also a workplace with patients, supervisors, and other professionals, which creates a complex learning environment. In PHC, students meet authentic patients as they come to PHC with they problems when the students participate in everyday clinical work. In order to ensure the quality of the learning environment in PHC and provide an opportunity for both the PHC centre and the university to receive up-to-date feedback, it is important that the students have access to an evaluation instrument. The instrument needs to measure several aspects of the learning environment.To ensure quality and the student's opportunity to progress in their journey towards a future profession, it is important to gain an understanding of how the clinical learning in PHC is perceived by students and patients and how it can be evaluated.AimsThe aim of Study I was to adapt and validate the Clinical Learning Environment and Supervision (CLES) instrument to measure medical students' perceptions of their learning environment in PHC. In Study II, the aim was to explore medical students' perceptions of the clinical learning environment in PHC and how these perceptions vary according to the stage in the education programme. In Study III, the aim was to explore the perceptions of ordinary patients in PHC when participating in encounters with medical students and what they believe they contribute to the students' learning. In Study IV, the aim was to explore medical students' perceptions of learning from patient encounters in a PHC context.MethodsIn Study I, the CLES instrument was adapted to measure medical students' learning environment in PHC. The CLES instrument, which contains 25 items, was sent electronically to 1,256 students in the medical programme over 9 semesters. The study used exploratory factor analysis based on the principal components method, followed by oblique rotation, to confirm the adequate number of factors in the data. Construct validity was assessed by factor analysis. Confirmatory factor analysis was used to confirm the dimensions of the CLES instrument. In Study II, content analysis was used to analyse the students' free text comments, which they wrote in connection with the usual evaluation of their learning environment. In Study II, an adapted CLES instrument was used as an evaluation instrument. Study III was a qualitative study where individual interviews were analysed by inductive content analysis. A total of 13 patients were interviewed immediately after they had met a medical student during their visit to the PHC centre. Study IV was a qualitative study that used individual interviews with a semi-structured interview guide. The data was analysed by inductive content analysis. In total, 21 medical students were interviewed.ResultsIn Study I, a total 394 of students answered the questionnaire. The construct validity showed a clearly indicated four-factor model. The cumulative variance explanation was 0.65. The overall Cronbach's alpha was 0.95. The adapted CLES instrument had high construct validity and reliability and high internal consistency. In Study II, the two main themes were 'The supervisor was the central factor in determining the meaningfulness of the placement at all stages of the education' and 'Basic prerequisites for perceived clinical learning were to having an active role in an authentic clinical context and being trusted to work independently with patients'. The three categories were 'The perceived relationship with the supervisor', 'The perceived journey to become a doctor' and 'The perceived structure and culture'. In Study III, one main theme was found: 'Participating in a dialogue adapted to students' needs without being aware of one's role as a teacher' and four categories: 'Expectations and conditions for participation', 'Contribution to learning', 'Collaboration in learning', and 'Perceived benefit for the patient'. In Study IV, the main theme was 'The individual patient encounters are the key to learning in PHC'. Four categories were found: 'Patient encounters in primary health care are instructive, rewarding, and challenging', 'Encounters with patients in PHC provide opportunities for gradual professional development', 'A committed supervisor plays a significant role in learning', and 'Learning in PHC and learning in hospitals complement one another'.ConclusionThe CLES evaluation instrument was adopted for medical students and was subsequently seen as a useful tool for their evaluation of the clinical learning environment in PHC. Students' perceptions and experiences of clinical practice in PHC showed that the supervisor and patient were important for the student's progression. Active participation in clinical work and patient encounters, and the mix of patients in PHC, were seen as important for the development of clinical and communication skills. Patients were not always aware of their role in the student's learning but were able to contribute in many ways. The patients adapted to the students and allowed the students to perform examinations at their own pace. Students felt responsible for the patient and sometimes felt uncertain about whether they had the necessary competence. Committed supervisors provided students with the confidence to act on their own, and the students were aware of their own development.List of scientific papersI. Öhman E, Alinaghizadeh H, Kaila P, Hult H, Nilsson G.H, Salminen H. Adaptation and validation of the instrument Clinical Learning Environment and Supervision for medical students in primary health care. BMC Medical Education. 2016. 16:308. https://doi.org/10.1186/s12909-016-0809-8II. Salminen H, Öhman E, Stenfors-Hayes T. Medical students' feedback regarding their clinical learning environment in primary healthcare: a qualitative study. BMC Medical Education. 2016. 16:313. https://doi.org/10.1186/s12909-016-0837-4III. Öhman E, Toth-Pal E, Hult H, Nilsson G.H, Salminen H. How patients in primary health care perceive their contribution to medical students' learning - an interview study. [Manuskript]IV. Öhman E, Toth-Pal E, Hult H, Nilsson G.H, Salminen H. Medical students' perception of learning from patient encounters in primary health care; a qualitative interview study. BMC Medical Education. 2023. 23:935. https://doi.org/10.1186/s12909-023-04923-9